Facile quantization of semiconductor compounds in the zeolite: characterization of quantum dots of Zn4S6+ and Zn2S2+ in zeolite Y. (March 2022) - Moon, D.J.; Park, M.; Lim, W.T.
Abstract: The extra-framework zinc sulfide cationic clusters, Zn4 S 6+ and Zn2 S 2+, have been introduced into zeolite Y (FAU, Si/Al = 1.56). The |Zn24.5 Na12 (Zn4 S 6+ )0.5 (Zn2 S 2+ )5.5 |[Si117 Al75 O384 ]-FAU was prepared by allowing aqueous 0.1 M Na2 S solution to flow past a |Zn37.5 |[Si117 Al75 O384 ]-FAU at 294 K for 2 days. Its structure was determined by single-crystal synchrotron X-ray diffraction techniques. The crystallographic study showed that one sulfide ion at the center of the sodalite cavity coordinates to four Zn 2+ ions at site I' to give a centered-tetrahedral cationic cluster, Zn4 S 6+, and the other sulfide ion opposite 6-ring in the sodalite cavity bridges between two Zn 2+ ions at site I' to give a cationic cluster with bent arrangement, Zn2 S 2+, in 6.3% and 68.8% of the sodalite cavity of zeolite Y, respectively. Through high-resolution transmission electron microscope image, zinc sulfide quantum dots (QDs) group with the size of one unit cell ( ca . 3 nm) in which hundreds were distributed was identified. By using UV–vis diffuse reflectance spectroscopy, it was confirmed that the zinc sulfide QDs occupied in the structure of zeolite Y exhibited enhanced optical activity because of the quantum size effect compared with that of bulk zinc sulfide. In this study, a method for quantizing semiconducting compounds in the cavity of zeolite Y was presented more easily, and its properties were investigated in more depth. The results proved that zeolite could be applied and used as a quantum container for the quantization of semiconductor compounds. Graphical abstract: Image 1 Highlights: The synthesis of Zn4 S 6+ and Zn2 S 2+ quantum dots (QDs) in the cavity of zeolite Y was attempted by metathesis reaction. The characterization of the zinc sulfide (ZnS) QDs in the cavity of zeolite Y was completed by SC-XRD, SEM-EDX, UV–vis spectroscopy, and HRTEM. SC-XRD analysis provided the three-dimensional structure of Zn4 S 6+ and Zn2 S 2+ in the cavity of zeolite Y. The differences in optical properties between bulk ZnS and ZnS QDs in the cavity of zeolite Y was compared. The hundreds of ZnS QDs group corresponding to the size of unit cell in the zeolite Y structure were identified.